Differentiating autism spectrum disorder and global developmental delay in preschoolers: overlapping profiles and diagnostic challenges - Sperandini, Veronica; Fucà, Elisa; Sbarbati, Martina; Schettino, Maria; Falvo, Stefania; Quarin, Fabio; De Rose, Paola; Vicari, Stefano (Frontiers in Psychology, 2025)
IntroductionDifferentiating Autism Spectrum Disorder (ASD) from Global Developmental Delay (GDD) in preschoolers may be challenging due to overlapping symptoms and shared developmental impairments. This study aimed to examine similarities and differences in adaptive functioning, emotional and behavioral characteristics, and autistic symptomatology in preschoolers with ASD and those with GDD presenting autistic traits.MethodsEighty-nine children aged 3 to 5.8 years (42 with ASD, 47 with GDD), matched for age, intelligence quotient, and sex, were assessed using the Adaptive Behavior Assessment System—Second Edition, the Child Behavior Checklist, and the Childhood Autism Rating Scale—Second Edition.ResultsGroup comparisons revealed no significant differences in adaptive functioning or emotional-behavioral symptoms, with both groups showing marked adaptive deficits and borderline levels of social withdrawal. In contrast, clear differences emerged in autistic symptomatology, although certain items (e.g., imitation, adaptation to change, listening response, sensory response, and fear or nervousness) did not differ significantly.DiscussionThese findings underscore the complexity of early differential diagnosis between ASD and GDD and emphasize the importance of enhanced clinician training and tailored early interventions to improve diagnostic accuracy and individualized care planning.